SWOT analysis of current state and prospects for the development of artificial intelligence in |Kazakhstani media industry (Herald of Journalism, 2022)
In case of Kazakhstan, there is a push for the widespread introduction of public information services and the modernization of management based on information technologies at the official state level. These services include the introduction of electronic government (egov.kz) and gradual digitalization of the public space as in the state program “Digital Kazakhstan”. The authors view the process of digitalization as a preliminary step towards introduction and implementation of various instruments based on artificial intelligence. Aim of the study is to examine the cases of application of various AI based tools in Kazakhstani media sphere. The scientific significance is due to the relevance of the topic, the interdisciplinary direction of work. Practical significance lies in the ability to use data in several scientific fields. Authors applied method of SWOT-analysis to examine the strengths, weaknesses, potential opportunities and threats of using electronic platforms based on various artificial intelligence tools in addition to the content analysis, which allows both for quantitative and qualitative sampling. It can be concluded that strengths of AI development in Kazakhstan include comparatively high level of digitization in comparison to other countries in the region. In order for Kazakhstan to use the full potential of artificial intelligence technologies and advanced analytics, it will also require a lot of joint efforts on the part of the state, private business and residents of the country. At the population level, we can talk about the formation of habits of using technology to facilitate everyday life, as well as the development of digital methods of work. This work contributes to understanding of the usage of AI based in technologies in various socio-economical spheres on Kazakhstan. The results of the study can be used in applied work on social journalism.Keywords: artificial intelligence, SWOT-analysis, information technology, media industry, “Digital Kazakhstan”.